Collective Ijtihad in the Disruption Era: a Thematic Analysis of Pbnu’s 2024 Fatwas in Responding to Global Challenges - Mohammad Adnan; Badrah Uyuni; Samsul Maarif (At Taawun Bangun Bangsa, 2025)
The era of global disruption—marked by climate change, geopolitical tensions, and digital transformation—demands fatwa institutions to formulate responses that are both textually sound and contextually relevant. This study analyzes Nahdlatul Ulama’s (NU) model of ijtihad jamā‘ī (collective ijtihad) as practiced in the 2025 Bahtsul Masail Munas Alim Ulama, focusing on six fatwa decisions issued in 2024. A qualitative descriptive approach with thematic analysis was applied to NU’s official documents, with the primary subject being the official Materi Munas Alim Ulama NU 2025 published by PBNU, which contains six fatwa decisions across the categories of Waqi’iyyah, Maudhu’iyyah, and Qanuniyyah. The findings show that PBNU integrates turāth scholarship, contextual analysis, and maqashid al-shari’ah to produce progressive rulings on issues such as carbon trading, zakat on banknotes, equitable hajj dam distribution, and global conflict. These fatwas function not only as legal responses but also as normative instruments influencing fiscal innovation, environmental policy, transnational worship governance, and broader sharia-based public discourse. Theoretically, this research enriches discourse on collective ijtihad by situating NU’s fatwas within global Islamic legal debates and highlighting their epistemic originality. Practically, it emphasizes PBNU’s growing potential as both a national policy contributor and a credible global reference for maqāṣid-oriented, culturally grounded fatwa authority.